5(5x-3)=4x-6

Simple and best practice solution for 5(5x-3)=4x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(5x-3)=4x-6 equation:


Simplifying
5(5x + -3) = 4x + -6

Reorder the terms:
5(-3 + 5x) = 4x + -6
(-3 * 5 + 5x * 5) = 4x + -6
(-15 + 25x) = 4x + -6

Reorder the terms:
-15 + 25x = -6 + 4x

Solving
-15 + 25x = -6 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-15 + 25x + -4x = -6 + 4x + -4x

Combine like terms: 25x + -4x = 21x
-15 + 21x = -6 + 4x + -4x

Combine like terms: 4x + -4x = 0
-15 + 21x = -6 + 0
-15 + 21x = -6

Add '15' to each side of the equation.
-15 + 15 + 21x = -6 + 15

Combine like terms: -15 + 15 = 0
0 + 21x = -6 + 15
21x = -6 + 15

Combine like terms: -6 + 15 = 9
21x = 9

Divide each side by '21'.
x = 0.4285714286

Simplifying
x = 0.4285714286

See similar equations:

| (12A^2B+A-5A^2B+2AB)-(4AB^2+6AB-2A-3AB)= | | v^2+5v+7vq+35q=0 | | 5(5x-3)=4x+6 | | 14+3n=-3(n-4) | | 16+.20x=30 | | -3y+28=ysq | | -2(w-7)+12w=34 | | 23c+20=29c+74 | | 8=17.666c | | 16+.20x=306 | | 6(x+3)=-5 | | 11.1x-3.3=-8.3x+6.4 | | A+2b=20+c | | 5y-2=-(y+5) | | 15-5w=75-10w | | (3x+7)(x+6)=0 | | 325x+6=421 | | (cos^2)(x)-(4)(cosx)-5=0 | | 3(4x+6)-5=12x+13 | | x^2+y^2+10x+2y+13=0 | | 2(2x)+2(x)=210 | | X+20=9x-4 | | 45.75x+3.50=35.95x+4.75 | | 2(a-6)+11=25 | | A+2b=20c | | y^2P^2+xP+y=0 | | factorisex^2+y^2+10x+2y+13=0 | | 3(2x-3)=5x-5 | | x^2+181=0 | | y^2P^2-xP-y=0 | | 25+3x=18 | | X-38=106 |

Equations solver categories